Strategi Komunikasi Pemasaran Terpadu pada Suratkabar Malaysia (Studi Deskriptif Harian Sinar Harian Selangor) - Razie Bin Nasarruddin; Anang Hermawan (Jurnal Komunikasi, 2010)
Sinar Harian has new comer daily newspaper in Selangor, and positioned as an independent newspapers. So, this media use marketing communication concepts in order to accepted by communities in their audience in Malaysia. The whole factor are become from their integrated marketing communication strategy (IMC), that have five indicators included advertising, personal selling, direct marketing, public relations and sales promotions as a promotional mix. Besides IMC strategy, Sinar Harian also make an IMC steps to high up their ranking at Malaysia newspaper industries. IMC steps have four indicators and it is identify market target, make SWOT analized, make a marketing communication goals and strategy with tactics arrangement After the research, researchers got the truth that Sinar Harian are threaten a promotional mix indicators like advertising, personal selling, direct marketing, public relations and sales promotion to get their profits and sold up the newspaper. Then the IMC steps are made for Sinar Harian make a strategy based on SWOT analyzed and the whole IMC steps indicators for their positioning at Malaysia newspapers industries.